Analisis Tingkat Kesehatan Bank Menggunakan Metode `Rgec’ Pada PT. Bank Central Asia Tbk. Periode 2019-2023 - Mochammad Rizal Muhaimin; Fathur Rohman (CV. ITTC INDONESIA, 2024)
This study aims to determine how the soundness of the Bank in the period 2019 - 2023. This type of research is descriptive research with quantitative approach. The variables used were risk profile as measured by the ratio of NPL and LDR, good corporate governance is measured through self-assessment results, profitability as measured by ROA and NIM, and Capital as measured by the ratio of CAR. The research results will show that the health level of BCA bank during the period before Covid in 2019 to 2023